1998
DOI: 10.1046/j.1471-4159.1998.71052034.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nuclear DNA Oxidation in the Brain in Alzheimer's Disease

Abstract: Multiple lines of evidence indicate that oxidative stress is a contributor to neuronal death in Alzheimer's disease (AD). The oxidative damage that occurs to DNA may play a role in both normal aging and neurodegenerative diseases, including AD. This is a study of the oxidative damage that occurs in nuclear DNA in the brains of AD patients and cognitively intact, prospectively evaluated, age-matched control subjects. Nuclear DNA from frontal, temporal, and parietal lobes and cerebellum was isolated from 11 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
251
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 441 publications
(258 citation statements)
references
References 27 publications
5
251
0
2
Order By: Relevance
“…As with lipid peroxidation and protein carbonyl markers, levels of 8-OHdG and other oxidized DNA bases in MCI are comparable to those observed in LOAD brain. Again, consistent with mtDNA's proximity to ROS generation in the mitochondria and the relatively limited DNA repair capacity in mitochondria the extent of oxidation in mtDNA is approximately 10-fold greater than in nDNA [94,95]. There have been a few studies of lipid peroxidation-derived aldehyde-DNA adducts.…”
Section: Autopsymentioning
confidence: 76%
“…As with lipid peroxidation and protein carbonyl markers, levels of 8-OHdG and other oxidized DNA bases in MCI are comparable to those observed in LOAD brain. Again, consistent with mtDNA's proximity to ROS generation in the mitochondria and the relatively limited DNA repair capacity in mitochondria the extent of oxidation in mtDNA is approximately 10-fold greater than in nDNA [94,95]. There have been a few studies of lipid peroxidation-derived aldehyde-DNA adducts.…”
Section: Autopsymentioning
confidence: 76%
“…Alzheimers disease; DNA repair; oxidative stress; oxidative DNA damage Alzheimer's disease (AD) has been associated with elevated oxidative DNA damage in the human brain (Gabbita et al, 1998). Base excision repair (BER), the main repair pathway for the removal of oxidative base modifications from DNA, plays a vital role in the development and maintenance of the central nervous system (Fishel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fig 2E, 2F, 3B, 3C). 8-oxoG, an abundant mutagenic oxidized purine, and 5-OH-C, an oxidized pyrimidine, were previously shown to accumulate to a greater extent in affected human AD brain regions relative to aged matched controls (Gabbita et al, 1998;Wang et al, 2005). Oxoguanine DNA glycosylase (OGG1), the primary enzyme for the repair of 8-oxoG (Klungland et al, 1999;de Souza-Pinto et al, 2001), was found to be decreased in expression and activity in human AD brain tissues (Lovell et al, 2000;Iida et al, 2002;Weissman et al, 2007).…”
mentioning
confidence: 99%
“…1 A number of factors have been thought to contribute redundantly to pathogenesis of AD, including unbalanced calcium homeostasis, cell-cycle proteins, excitatory amino acids, as well as DNA damage. [2][3][4][5] However, deposit of bamyloid protein (bAP) in the brain parenchyma appears as the crucial factor in the onset of AD, 6 although mechanisms underlying bAP effects are far from elucidation, thus needing further investigation. For example, it has been hypothesized that proinflammatory cytokines, such as interleukin-1 and tumour necrosis factor-a (TNF-a), could partly promote neurodegenerative processes depending upon bAP.…”
Section: Introductionmentioning
confidence: 99%